Bioeconomics of aquaculture (Distributors for the U.S. and Canada, Elsevier Science Pub. Co., 1984)
This book describes the general principles and specific examples of modelling aquacultural production processes. Bioeconomic modelling combines two disciplines (applied economics and applied biological science) and its use in analysing optimal management decisions in aquacultural production is relatively new compared with agriculture. Containing published and unpublished work by the authors and other studies appearing in the literature, the book discusses modelling philosophies and provides workable approaches to the construction and testing of quantitative models. Necessary economic concepts are illustrated, specific types of biological and environmental responses with examples, are described, as are technical engineering functions applicable to aquacultural production. Final chapters give a selection of concise examples of bioeconomic modelling, often drawn from relatively inaccessible reports. Researchers conducting experiments on aquatic species wishing to express their results in quantitative responses, and aquacultural and fisheries economists working with biological response functions will find the book very useful.